Calvin's Interpretation of Christ's Agony at Gethsemane: An Erasmian Reading? - Essary, Kirk (Toronto journal of theology, 2014)
This paper considers the prospects of Erasmus's De taedio Iesu—an embellished recreation of a debate between Erasmus himself and John Colet at Oxford in 1499 over the question whether Christ truly feared for his own death in the Garden of Gethsemane—as an influence on John Calvin's interpretation of Matthew 26:37-39 and parallels in his Commentary on the Gospel Harmony (1555). It examines three aspects that Calvin's commentary shares with Erasmus's De taedio: (1) the use of a passage from Ambrose's Expositio in Lucam, (2) the problem of monothelitism and the two wills of Christ, and (3) the difference between Christ's passions and ours in light of original sin.